Additionality and Sustainable Development Issues Regarding CDM Projects in Energy Efficiency Sector - Axel Michaelowa; K. Umamaheswaran (Hamburg Institute of International Economics (HWWA), 2006)
The objective of this discussion paper is to assess additionality and sustainable development issues of energy efficiency CDM projects with an emphasis on the situation in India. In the second half of 2005, almost 100 energy efficiency projects has been submitted for validation and 54 of those projects were analysed with regards to additionality and sustainable development benefits based on Activity Scale (Large Scale & Small Scale), Sector (WHR, DSM, Cement Blending, Service), project start date. 60% are large scale projects and 90% had started before 2005. The results show that additionality and sustainable development are often assessed in a cursory manner and only in few projects additionality was well established. Besides resource conservation, energy efficiency projects do not create much qualitative sustainable development benefits on the whole. Technology transfer occurred rarely and indigenous technology development happened only in 2 projects.
Keywords: Q58; Q54; 330; Energy Efficiency Projects; Additionality; Sustainability Development; Large Scale; Small Scale Projects